Quality Management and Qualification Needs 2 Towards Quality Capability of Companies and Employees in Europe - Köper, Johannes; Zaremba, Hans J. (Physica-Verlag HD, 2000)
A research network has examined how quality management is implemented in small and medium sized enterprises (SMEs) in Europe and what the consequences are for the qualification needs of employees. The research has taken place within the framework of the Leonardo Da Vinci programme, which is an action programme of the European Commission DG XXII - Education Training and Youth. The survey results in the metalworking and food processing industries are published under the title Quality Management and Qualification Needs 1. Quality and Personnel Concepts of SMEs in Europe". This book presents conclusions including three parts: "Results" deriving from the sector studies - specialised "Scientific contributions" of network partners - "Action-oriented dialogue" documenting comments of key actors in vocational training from the participating countries. Special objectives are: - Support of quality-oriented development of SMEs and their staff - Support of quality-oriented development of vocational education and training - Description of implementation requirements including regional aspects